Protocol no. 14 and the reform of the European Court of Human Rights - Lemmens, Paul.; Vandelhole, Wouter (Antwerpen : Intersentia, 2005)
Chapter I. Protocol no. 14: object, purpose and preparatory.
work.
Chapter II. Organisation of the European Court.
Chapter III. Individual complaints.
Chapter IV. Friendly settlements and striking out of applications.
Chapter V. Execution of judgments.
Chapter VI. European Union accession to the European Convention on Human Rights.
Keywords: International law; International courts; Regional human rights protection systems; Legal proceedings; Europe; Complaints; European Convention on Human Rights; EU; ECHR-P14.